Trabalho docente e saúde: estudo de caso realizado no Centro Federal de Educação Tecnológica de Minas Gerais - Mota, Rosália Monteiro (2010)
The focus of this Dissertation is the teaching profession and the relationship between this activity and the teachers health. As the picture that emerges is complex, it would also be impossible or fallacious to draw a generalized picture of the teachers profile, their teaching profession and their working condition. For this, we decided to realize a study case anchored in a qualitative research, by choosing The Federal Center of Technological Education of Minas Gerais CEFET-MG, Campus I from Belo Horizonte, as the locus of this research. This choice seemed to be strategic as the Institution offers mid-level professional, undergraduate and graduate courses. Therefore, as a large teaching staff is presented, the teachers profile is diversified as to the graduation and training area, the performance area, the working time, the teaching time and the working conditions in the Institution, among others. Our target was to verify which are the impacts of the working conditions at CEFET-MG on the teachers health. For this research, the semi-structured interview and the document analysis were used. Teachers who are part of the permanent staff in full-time basis, from different areas and disciplines and with variable time teaching, were interviewed. Besides, teachers who work as coordinators and as Medical Dental professionals were also interviewed and relevant documents were consulted. The literature review has shown a growing interest, although by sector, on issues involving the teaching profession. Our research revealed that there are teachers involved in the classroom teaching and in research projects, with a high degree of qualification, who are pleased with their professional choice and willing to remain in that condition. However, reports from teachers, in comparison to the interviews held in the Medical Dental Department of the Institution, show signs of wear and illness, especially due to the current conditions surrounding the organizational structure and the increasing of labor demands, to which they need to adapt. The literature on teaching in general shows the same signs of wear and illness. In the case of the Institution studied in this Dissertation, wear and professional valorization alternate in the same narratives, revealing the involvement of teachers and that enable us to suggest some debates and the implementation of policies for short, medium and long term in order to enhance the teacher headcount. We believe that the Institution has both potential and human resources to invest in the enhancement of the teachers health in all its dimensions